Loupes-Only Microsurgery is a Safe Alternative to the Operating Microscope: An Analysis of 1,649 Consecutive Free Flap Breast Reconstructions - Pannucci, Christopher J.; Basta, Marten N.; Kovach, Stephen J.; Kanchwala, Suhail K.; Wu, Liza C.; Serletti, Joseph M. (Journal of Reconstructive Microsurgery, 2015)
Background Loupes-only microsurgery challenges the paradigm that free flap surgery requires an operating microscope. We describe our loupes-only microsurgery experience with an emphasis on rates of intraoperative anastomotic revision and total flap loss.Methods We identified all patients having breast reconstruction with muscle-sparing transverse rectus abdominis myocutaneous (ms-TRAM) or deep inferior epigastric perforator (DIEP) flaps over 7 years. We examined rates of intraoperative anastomotic revision and total flap loss as markers of technical quality. For one high-volume surgeon who started loupes-only microsurgery while at our institution, we examined rates of intraoperative anastomotic revision and total flap loss rates over time to evaluate for a learning curve.Results We performed 1,649 ms-TRAM or DIEP flaps in 1,063 patients. For 1,649 flaps, the rate of artery anastomotic revision was 2.2% (36 arteries) and venous anastomotic revision was 2.2% (37 veins). Any microvascular revision was performed in 3.5% (58 flaps). Total flap loss rate was 1.2% (20 flaps).For the “learning curve” analysis, there were no clinically relevant differences in rates of any intraoperative anastomotic revision or total flap loss during the first 60 months after loupes-only microsurgery was adopted. Total flap loss during this surgeon's first 60 months of loupes-only microsurgery was 1.6% (10 of 638 flaps).Conclusions Loupes-only microsurgery is a safe alternative to the operating microscope for free flap breast reconstruction using the deep inferior epigastric system. Our total flap loss rate of 1.2% in 1,649 flaps is at the low end of published flap loss rates.
Keywords: loupes; microscope; free flap; breast reconstruction; TRAM; DIEP